eM-Age (excel Macro for Age calculation), a new application for luminescence age calculation based on Dose Rate and Age Calculator (DRAC) and Analyst - Pérez-Garrido, C. (Ancient TL, 2020)
eM-Age is a new program for calculating luminescence ages quickly and more easily. It allows the user to instantly check the impact of choosing different attenuation factors (dose rate parameters, grain size, water content, etc) on the final dose rate, and therefore also on the final age, calculation. Based on data collected by Durcan et al. (2015) in the DRAC program, eMAge offers a graphical interface and also allows the calculation and selection of equivalent dose data from summaries generated by Analyst, as well as offering options for different age models for the loaded data